Improvement of yield and nutrient composition of orchardgrass in soils with increased nickel concentration by inoculation with Bacillus strains - Buntić Aneta; Stajković-Srbinović Olivera; Pešić Mila; Dinić Zoran; Milinković Mira; Knežević Magdalena (Zemljište i biljka)
The pollution of soil by potentially toxic trace elements (PTE) is increasing every year and has become a serious problem worldwide. Plant growth is influenced by numerous interactions with the environmental factors and organisms from the surrounding soil, including high concentration of PTE. The aim of this research was to evaluate the possibility of growing orchardgrass in soils with an increased Ni concentration and improvement of the plant quality in these stressful conditions using Bacillus inoculums. In addition, the plant growth promoting traits and the germination of inoculated Dactylis glomerata seeds with Bacillus inoculants was examined. The main goal was to examine the effects of inoculums on plant yield, nutrient composition, and trace elements concentration in orchardgrass biomass. The ability of bacterial isolates to tolerate high concentration of Ni as well as the potential of these bacteria to enhance the germination of orchardgrass seeds was tested in vitro on Petri dishes. A pot experiment was conducted in soil with elevated Ni concentration, and plant dry mass, as well as the content of micro and macro elements in plant material was determined. The results of the pot experiment showed the positive effect of bacterial inoculation on shoot dry weight of orchardgrass, while the nitrogen content in orchardgrass shoots was slightly increased under the influence of bacterial inoculation. Furthermore, the content of microelements in plant material was reduced in inoculated plants.